2011
DOI: 10.1097/inf.0b013e31822d1451
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Plasmodium falciparum Erythrocyte-binding Antigen-175 are Associated With Protection From Clinical Malaria

Abstract: Background Antibodies to blood-stage Plasmodium falciparum antigens have been associated with protection against clinical malaria in some studies but not others. Many of these studies have not assessed whether high-titer antibodies are associated with protection and have not adjusted for differences in malaria exposure. Methods The presence of high-titer antibodies to apical membrane antigen-1 (AMA-1), erythrocyte binding antigen-175 (EBA-175) and merozoite surface protein-119 (MSP-119) was assessed in 87 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
(56 reference statements)
3
26
0
Order By: Relevance
“…Another study also reported that high IgG4 levels specific for blood-stage antigens were associated with an enhanced risk of infection and malaria attacks (4). Findings are consistent with those from recently published studies in which high levels of IgG (particularly IgG1 and IgG3) to EBA antigens were associated with protection from malaria (26,42). Other studies failed to find an association between responses to EBA-175 and the incidence of P. falciparum malaria (22,34,36), although Okenu et al (34) reported a protective trend for high levels of IgG to region II (which includes F2, used in our study).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another study also reported that high IgG4 levels specific for blood-stage antigens were associated with an enhanced risk of infection and malaria attacks (4). Findings are consistent with those from recently published studies in which high levels of IgG (particularly IgG1 and IgG3) to EBA antigens were associated with protection from malaria (26,42). Other studies failed to find an association between responses to EBA-175 and the incidence of P. falciparum malaria (22,34,36), although Okenu et al (34) reported a protective trend for high levels of IgG to region II (which includes F2, used in our study).…”
Section: Discussionsupporting
confidence: 86%
“…Recent work has shown an association between IgG to EBA-175 and protection from malaria (26,42). However, conflicting evidence in immunoepidemiological studies and unsuccessful phase IIb vaccine trials question the extent of the relevance of AMA-1 and MSP-1 in protection against malaria (33).…”
mentioning
confidence: 99%
“…A statistical modeling approach combined with highly sensitive molecular techniques using an all-age cohort in Ghana -an area of high P. falciparum transmission -estimated that untreated asymptomatic infections had a mean duration of 194 days (95% CI: 191-196) [58]. In areas of highly seasonal transmission, low-density asymptomatic infections are believed to persist over the course of the dry season and to reseed transmission when mosquito populations increase along with wetter conditions [59,60]. P. malariae has been found in at least one case to remain asymptomatic for decades [61].…”
Section: How Long Do Asymptomatic Infections Last?mentioning
confidence: 99%
“…We further investigated differences in antibody associations between the two cohorts by comparing IgG responses to the EBAs, which are merozoite invasion ligands and emerging as important targets of acquired immunity (12,23,37,53,54). Prior studies observed that IgG antibodies against the EBAs were among the responses most strongly associated with protective immunity in the cohort of older children, even after adjusting for potential confounders (23,44).…”
Section: Figmentioning
confidence: 99%